Marine Sand Borrows in Western Cyprus: Distribution and Potential Prospects - Hasiotis, Thomas; Petsimeris, Ivan Theofilos; Chtouris, Nikolas-Kimon; Andeadis, Olymbos; Velegrakis, Adonis; Mettas, Christodoulos (My University, 2024)
Marine sands are considered critical resources for beach replenishment purposes as well as for the construction industry, and their demand is expected to expand due to the anticipated sea-level rise and climate change. In the Republic of Cyprus, coastal erosion is a long-term problem that is predicted to intensify, posing into a great danger the 142 narrow but mainly sandy beaches that support the travel and tourism industry of the country. Against this background, the western offshore part of Cyprus was investigated in order to detect potential sand borrows that could support, at least, beach sustainability in the region. The study was concentrated into two areas where data collection (single-beam bathymetry, side scan sonar imagery and surficial seabed sampling) took place. The analysis designated four neighboring blocks down to 50 m depth and over an area ~40 km long, with a total volume of ~7.5 x 106 m3 of material (for abstraction only of the surficial layer-0.5 m), consisting of coarse to fine sand with the majority being medium to fine sands. Taking into account that Coral Bay, one of the most touristic beaches in west Cyprus, comprises of similar grain-size sands, and that under the worst case scenario of long-term sea-level rise it might require about 120000 m3 for a single beach replenishment, it becomes evident that the detected borrows are of sufficient quantity to cover repeated nourishment schemes not only of one but of numerous similar beaches in Cyprus. The observed deposits can lead further necessary detailed geological and environmental studies so as to evaluate the prospect of the deposits. Marine sand borrows detection and potential exploitation in Cyprus could also boost national blue economy actions and improve human well-being, preserving the environment.
Keywords: Marine aggregates; geophysical prospecting; coastal management; beach nourishment; western Cyprus.